Implementation of Industrial Design Rights Registration of Bone Carving Handicrafts in Tampaksiring Tourism Village of Gianyar District - Anak Agung Sagung Ngurah Indradewi; I Wayan Partama Putra; Cok Gede Nata Wasistha (Universitas Dwijendra Press, 2024)
The design of bone carving crafts in Tampaksiring tourist village of Gianyar Regency needs to be protected to ensure the protection of the rights of the designer and establish its rights and obligations as well as to keep unauthorized parties from misusing the industrial design. This is in accordance with Article 10, 11, 12 of Law Number 31 Year 2000 on Industrial Design. However, in its implementation, not all bone designs have received protection of Industrial Design Rights, so it is important to raise the issue: Implementation of Registration of Industrial Design Rights to obtain Legal Protection of Bone Carving Crafts in Tampaksiring Tourism Village. This study aims to analyze the legal protection of industrial design rights against bone carving crafts in Tampaksiring tourism village. The formulation of the problem in this study is 1). How is the implementation of industrial design rights registration against bone carving crafts in Tampaksiring tourist village, Gianyar regency? 2). How is the effectiveness of legal protection of industrial design rights to bone carving crafts in Tampaksiring tourist village, Gianyar regency. This research method uses the type of empirical legal research with qualitative analysis, with Non-Probability Sampling technique and by using Purposive sampling method which is described by using the theory of legal effectiveness, the theory of legal position, the theory of legal authority and the theory of legal protection. The conclusion of this study is the implementation of industrial design registration of bone carving crafts in Tampaksiring tourist village of Gianyar Regency is evident from the small awareness of individual craftsmen to register industrial design rights of craft products produced due to factors affecting the implementation of industrial design registration in the bone craft industry in Tampaksiring tourist village of Gianyar Regency, due to lack of awareness of craftsmen and lack of coordination and socialization regarding the importance of registration of industrial design rights to obtain legal protection. The effectiveness of legal protection of industrial design rights to bone carving crafts in Tampaksiring tourist village is not effective and optimal, it is caused by the mindset of craftsmen who think the process of registering industrial design rights is not too important and does not really affect the production of crafts produced, so that when a problem arises related to violations of industrial design rights in this case plagiarism of bone carving designs, then the law does not have the authority to take action against such violations and legal protection of the carving crafts cannot be realized because the bone carving crafts do not have legal legality. Bone Carving Craftsmen in Tampaksiring Village, Gianyar Regency think that the Certificate of Industrial Design Rights has not guaranteed legal protection for holders of industrial design rights which are their exclusive rights so that there are still many doubts of craftsmen who think that registration of industrial design rights is not too important to do